Genre Publics : Popular Music, Technologies, and Class in Indonesia - Baulch, Emma, 1968- (Book collections on Project MUSE., 2020)
"An exploration of how pop music's increasing popularity helped to develop Indonesia as a global center, recognized both by other global powers and Indonesians themselves"--